Scientific Opinion on the setting of health‐based reference values for metabolites of the active substance terbuthylazine - Hernandez‐Jerez, Antonio F (EFSA J, 2019)
The EFSA Panel on Plant Protection Products and their Residues was requested to establish health‐based reference values for groundwater metabolites (LM2, LM3, LM4, LM5 and LM6) of the active substance terbuthylazine based on the available evidence, unless the evidence was considered insufficient to do so. The request was accepted under the explicit circumstance that the reassessment would be made according to a different methodology than the routine methodology currently applied for the assessment of metabolites in groundwater. While for metabolites LM2, LM4 and LM5, it was concluded that the reference values for terbuthylazine are applicable, substance‐specific reference values could not be derived for metabolites LM3 and LM6. The applied threshold of toxicological concern (TTC) approach has shown that metabolites LM3 and LM6 are of potential concern for consumer health, since at least one representative groundwater leaching scenario results in exposure above the relevant threshold. Moreover, other sources of exposure to LM3 and LM6 could not be excluded with certainty. It is therefore recommended to address the specific toxicities of metabolites LM3 and LM6.